HAND ECZEMA AND ITS IMPACT ON WELLBEING AND QUALITY OF LIFE OF PATIENTS - Filka Georgieva (Peytchinski Publishing, 2017)
Hand eczema (HE) is a common skin condition with a chronic course. Both genetics and contact allergens triggers this form of eczema. It often affects people who work in cleaning, catering, hairdressing, healthcare and mechanical jobs where they may come into contact with chemicals or other irritants. The aim of the study is to assess the impact of hand eczema on quality of life (QoL). Material and methods: The presented study includes 78 out-patients diagnosed with HE. Demographic data and disease-related characteristics were collected. For the evaluation of QoL Dermatological Life Quality Index (DLQI) questionnaire was applied. Disease severity was assessed by hand eczema severity index (HECSI) score. Result and discussion: HE is more common in female 67, 94% than in male 32, 06%. The mean age of the patients was 34.14±12.16 years with range from 16 years to 52 years. The total DLQI score reported by the patients with hand eczema is 10.3±4.19 (median 11.00; IQR 4.00-26.00). Patients' scores were high for all questions (p<0,001) with the exception of Q4 (cloths) and Q10 (treatment). High scores was for Q1 (feelings), Q2 (embarrassment), Q3 (daily work), Q8 (relationship) and Q9 (sexual). The highest scores was for Q7 (job). Conclusion: All the reported and analyzed results indicate that HE has a negative impact on all the QoL-domains for majority of patients (p<0.001).